Prenatal nicotine and maternal deprivation stress de-regulate the development of CA1, CA3, and dentate gyrus neurons in hippocampus of infant rats. - Hong Wang; Marjorie C Gondré-Lewis (PLoS ONE, 2013)
Adverse experiences by the developing fetus and in early childhood are associated with profound effects on learning, emotional behavior, and cognition as a whole. In this study we investigated the effects of prenatal nicotine exposure (NIC), postnatal maternal deprivation (MD) or the combination of the two (NIC+MD) to determine if hippocampal neuron development is modulated by exposure to drugs of abuse and/or stress. Growth of rat offspring exposed to MD alone or NIC+MD was repressed until after weaning. In CA1 but not CA3 of postnatal day 14 (P14) pups, MD increased pyramidal neurons, however, in dentate gyrus (DG), decreased granule neurons. NIC had no effect on neuron number in CA1, CA3 or DG. Unexpectedly, NIC plus MD combined caused a synergistic increase in the number of CA1 or CA3 neurons. Neuron density in CA regions was unaffected by treatment, but in the DG, granule neurons had a looser packing density after NIC, MD or NIC+MD exposure. When septotemporal axes were analyzed, the synergism of stress and drug exposure in CA1 and CA3 was associated with rostral, whereas MD effects were predominantly associated with caudal neurons. TUNEL labeling suggests no active apoptosis at P14, and doublecortin positive neurons and mossy fibers were diminished in NIC+MD relative to controls. The laterality of the effect of nicotine and/or maternal deprivation in right versus left hippocampus was also analyzed and found to be insiginificant. We report for the first time that early life stressors such as postnatal MD and prenatal NIC exposure, when combined, may exhibit synergistic consequences for CA1 and CA3 pyramidal neuron development, and a potential antagonistic influence on developing DG neurons. These results suggest that early stressors may modulate neurogenesis, apoptosis, or maturation of glutamatergic neurons in the hippocampus in a region-specific manner during critical periods of neurodevelopment.